Migrating and Settling in a Mobile World: Albanian Migrants and Their Children in Europe (2015)
Comparative research on migration is a growing trend in academia. Yet very few studies that compare migrants and their descendants across different sites exist. Study of the integration of the children of migrants—the so-called ‘second-gener- ation’—is itself a recent trend in social science research and migration literature. Their integration is thought to be an important indicator of the degree of integra- tion of immigrants into a specific society. This book offers an in-depth, qualitative analysis of the integration of Albanian migrants and their descendants in Europe. It is also the first full-length comparative study of the Albanian ‘second-generation’. Using a variety of field methods, it compares the ethnic identities, transnational ties and integration pathways of Albanian migrants and Albanian-origin teenagers in three European cities—London, Thessaloniki and Florence—by focusing on inter- generational transmission between the first and the second generation. Greece, Italy and the UK are, in that order, the three main European countries where Albanian migrants have settled during their short but intense migration experience of the past two decades. This book shifts the focus partly to the situation and developments in Southern Europe, where awareness of and interest in issues of integration of the second-generation are still at an early phase. By studying a settling immigrant group and their descendants, this book takes a proactive approach towards the integration of ethnic minorities.